2021
DOI: 10.3390/sym13010085
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Time Delay on Controlling the Non-Linear Oscillations of a Rotating Blade

Abstract: Time delay is an obstacle in the way of actively controlling non-linear vibrations. In this paper, a rotating blade’s non-linear oscillations are reduced via a time-delayed non-linear saturation controller (NSC). This controller is excited by a positive displacement signal measured from the sensors on the blade, and its output is the suitable control force applied onto the actuators on the blade driving it to the desired minimum vibratory level. Based on the saturation phenomenon, the blade vibrations can be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This mechanism is called tuning mechanism discussed before in Refs. [6,[8][9][10]24], or in other words if is tuned at one half of the rotor speed Ω (Ω = 2 ). This can be implemented by providing the NSC control unit with the measured rotor speed Ω from a shaft encoder device shown in Fig.…”
Section: Vibrational Performance Of the Rotor-ambs In Response To Nscmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is called tuning mechanism discussed before in Refs. [6,[8][9][10]24], or in other words if is tuned at one half of the rotor speed Ω (Ω = 2 ). This can be implemented by providing the NSC control unit with the measured rotor speed Ω from a shaft encoder device shown in Fig.…”
Section: Vibrational Performance Of the Rotor-ambs In Response To Nscmentioning
confidence: 99%
“…This time-delayed NSC was quadratically coupled to the main system, then the time delays effects on the system behavior and stability were studied. Kandil et al [9,10] applied the NSC to the first mode only of a thin-walled rotating beam due to the strong coupling between the first and second modes. They adopted the multiple scales method for extracting the steady-state equations so as to describe the system behavior under the action of NSC.…”
Section: Introductionmentioning
confidence: 99%
“…It shares parameters between multiple output Gaussian distributions during training and measures the similarity between input samples in a new embedding space to reduce bias and improve overall prediction accuracy [16]. For actively controlling non-linear blade vibrations, a rotating blade's non-linear oscillations are reduced via a time-delayed, non-linear saturation controller (NSC) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Te research indicated that the softening nonlinearity of the studied rotating beam with thermal barrier coatings was enhanced according to the rise of temperature. Hamed and Kandil [25] focused on the timedelay efects of the saturation phenomenon that existed in the control of a vibratory rotating beam. Tey gave timedelay criteria for a safe system operation in order to exhibit a stable bounded beam's behavior.…”
Section: Introductionmentioning
confidence: 99%